The origin of ideas in the 'Paper for the People': research into how the Sunday Times chooses topics and commentators for its opinion pages - Serino, T. Kenichi (My University, 2009)
Abstract The topics in the opinion pages of newspapers are the substance of much public debate and discussion. This research report focuses on the Sunday Times, one of South Africa's most influential newspapers, and seeks to understand how columnists and issues are chosen for its opinion and analysis pages. The research was conducted by interviewing decision-makers at the Sunday Times, observing them during their meetings and conducting a content analysis of the newspaper. The findings identify journalistic professional practice as a key element in the selection process, along with an awareness of, and to some extent, identification with, a national project of transformation in a post-repressive regime. The findings also point to how issues of transformation in South Africa affect how media decision-makers consider their own jobs and motivates them to make conscious efforts to push the media agenda forward in a way constructive to public discourse.